Use of mobile phones in an emergency reporting system for infectious disease surveillance after the Sichuan earthquake in China - Changhong Yang; Jun Yang; Xiangshu Luo; Peng Gong
PROBLEM: Quick detection and response were essential for preventing outbreaks of infectious diseases after the Sichuan earthquake. However, the existing public health communication system in Sichuan province, China, was severely damaged by the earthquake. APPROACH: The Chinese Center for Disease Control and Prevention set up a mobile phone emergency reporting system. In total, 495 light-powered mobile phones were delivered to local health-care agencies in earthquake affected areas. All phones were loaded with software designed for inputting and transmitting cases of infectious disease directly to a national database for further analysis. LOCAL SETTING: The emergency reporting system was set up in 14 counties hit hardest by the earthquake in Sichuan province, China. RELEVANT CHANGES: One week after delivering mobile phones to earthquake-affected areas, the number of health-care agencies at the township level that had filed reports returned to the normal level. The number of cases reported by using mobile phones accounted for as much as 52.9% of the total cases reported weekly from 19 May to 13 July in those areas LESSONS LEARNED: The mobile phone is a useful communication tool for infectious disease surveillance in areas hit by natural disasters. Nevertheless, plans must be made ahead of time and be included in emergency preparedness programmes.